Understanding the Semantic System by Tehrani Residents from a Private Spacial Perception - Seyed Hasan Hosseini; shahla teymournejad (توسعه اجتماعی)
This qualitative study was conducted with the aim of understanding the semantic system by Tehrani residents from a private spacial perception. The method used in this research is the Grounded Theory as it is one of the main methods in qualitative research. The data of this study was collected through in-depth interviews and theoritical-purposeful sampling method with forty-two related residents and for analyzing data, five methods of open coding and recognition of concepts, development of concepts in terms of dimensions and characteristics, data analysis using grounded theory, inserting the process into the analysis, and integration of categories were used. The emerging paradigm consists of three dimensions of conditions, actions-interactions, and consequences which are based on the results of research in terms of dimensions involving (discovery of privacy dimensions, the transformational processes, the imposed limitations of lifestyle), in actions-interactions (the challenges of privacy, reconsideration, and redefinition of privacies), and in consequences dimension (institutional inefficiency in protecting the established privacies, incongruent interpretation of privacy in public areas) which revolves around a core category called (privacy with fluid boundaries in Iranian suspended society).